Effect of a mobile application promoting HIV prevention on knowledge of the benefits and uptake of HIV testing in Lagos, Nigeria - Kolawole, Oluwatoyin Olasimbo (Stellenbosch : Stellenbosch University, 2014)
Thesis (MPhil)--Stellenbosch University, 2014.